THE MODERN TRENDS IN FUTURE FOREIGN LANGUAGE TEACHERS` TRAINING TO ICT USAGE IN THEIR FUTURE CAREER - Proshkin, Vladimir; Glushak, Oksana; Mazur, Nataliia (The Modern Higher Education Review, 2018)
The analysis of competences that should be formed in the future foreign language teachers by the tools of modern information and communications technologies is presented by the authors. It is been determined that generic (core) competences include: informatics, informational, organizational and methodological competences; profile (specific) competences include the abilities of information and communications technologies usage for such pupils` skills forming as: listening, speaking, reading and writing. The program of electronic study course to support the realization of above-mentioned task is presented. The purpose of the program is to create a modern level of informational and computer culture, acquiring practical skills of application information technologies by teachers and philologists in order to increase the efficiency of the educational process; students of philological specialties and their preparation for the pedagogically effective use of information technology training in further professional activities. The content of the program modules has been given. Module 1. Network technologies in foreign languages, module 2. Office technologies in foreign languages, module 3. Multimedia technologies. The stages of using ICT in education have been identified, they are search, analysis and research of information, software, methodological resources for a lesson preparation with the further discussion; planning of organizational and methodological measures aimed at achieving goals and objectives of a certain lesson type; developing information materials according to the topic and type of lesson using ICT tools; assessment of future foreign language teachers readiness for the introduction of informational materials on the basis of software resources into the learning process. The usage of ICT for listening, speaking, reading and writing skills forming is demonstrated on the examples of software, on-line services and various podcasts.